2022
DOI: 10.1186/s12889-022-14767-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of supply sources of alcohol and alcohol-related harms in adolescent drinkers: the baseline characteristics of a high school cohort across Thailand

Abstract: Background The main objective of this study was to investigate the association between parental supply of alcohol, alcohol–related harms, and the severity of alcohol use disorder in Thai 7th grade middle school students. Methods A cross–sectional descriptive study obtained the baseline data from the project named the Thailand Parental Supply and Use of Alcohol, Cigarettes & Drugs Longitudinal Study Cohort in Secondary School Students in 2018. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The total prevalence of parental supply of alcohol among all minors ranged from 17.0 to 22.0% in England ( Health and Social Care Information Centre, 2011 , 2013 , 2015 , 2017 , 2019 ), 31.1 ( Stafström, 2014 ) to 41.7% ( Berge et al, 2016 ) in Sweden, 9.3 ( Mattick et al, 2017 ; Boland et al, 2020 ) to 45.2% ( Shaw et al, 2018 ) in Australia and was reported as 22.1% in the USA ( Murphy et al, 2021 ). Among only minors who reported drinking alcohol, prevalence rates ranged from 10.8 ( King et al, 2016 ; Vidourek et al, 2018 ) to 22.4% ( Jackson et al, 2016 ) in the USA, 20.9 ( Lam et al, 2017a , b ) to 43.0% ( Guerin and White, 2020 ) in Australia and were reported as 18.2% in Canada ( Wilson et al, 2018 ), 34.0% in Argentina ( Pilatti et al, 2013 ), 41.5% in Thailand ( Prasartpornsirichoke et al, 2022 ) and 60.1% in New Zealand ( Clark et al, 2013 ; King et al, 2016 ; Vidourek et al, 2018 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total prevalence of parental supply of alcohol among all minors ranged from 17.0 to 22.0% in England ( Health and Social Care Information Centre, 2011 , 2013 , 2015 , 2017 , 2019 ), 31.1 ( Stafström, 2014 ) to 41.7% ( Berge et al, 2016 ) in Sweden, 9.3 ( Mattick et al, 2017 ; Boland et al, 2020 ) to 45.2% ( Shaw et al, 2018 ) in Australia and was reported as 22.1% in the USA ( Murphy et al, 2021 ). Among only minors who reported drinking alcohol, prevalence rates ranged from 10.8 ( King et al, 2016 ; Vidourek et al, 2018 ) to 22.4% ( Jackson et al, 2016 ) in the USA, 20.9 ( Lam et al, 2017a , b ) to 43.0% ( Guerin and White, 2020 ) in Australia and were reported as 18.2% in Canada ( Wilson et al, 2018 ), 34.0% in Argentina ( Pilatti et al, 2013 ), 41.5% in Thailand ( Prasartpornsirichoke et al, 2022 ) and 60.1% in New Zealand ( Clark et al, 2013 ; King et al, 2016 ; Vidourek et al, 2018 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Argentina) ( Pilatti et al, 2013 ) and two studies from Asia (i.e. Thailand and South Korea) ( Asante et al, 2014 ; Prasartpornsirichoke et al, 2022 ). As only English-language studies were included in the review, it is possible that additional studies from these regions were not identified in our searches.…”
Section: Discussionmentioning
confidence: 99%